PENGARUH DUKUNGAN SOSIAL DAN EFIKASI DIRI DALAM PENCARIAN KERJA UNTUK MENCIPTAKAN ADABTABILITAS KARIER PADA MAHASISWA TINGKAT AKHIR FAKULTAS EKONOMI UNIVERSITAS NAHDLATUL ULAMA SIDOARJO - Aufa Izzudin Baihaqi; Jeziano Rizkita Boyas; Nafia Ilhama Qurratu'aini (Universitas Nahdlatul Ulama Sidoarjo, 2022)
This research was conducted at the University of Nahdlatul Ulama Sidoarjo. This study aims to identify how much influence Social Support and Self-Efficacy have in job search to create Career Adaptability for final year students at the Faculty of Economics, Nahdlatul Ulama University, Sidoarjo. This research uses quantitative research methods and data processing is carried out using SPSS software. In this case, Social Support and Self-Efficacy in job search are independent variables, while Career Adaptability is the dependent variable. This study used 100 final year student respondents. The results of data processing obtained Social Support beta value of 0.686 with a sig value. of 0.000, the value of sig. 0.000 < 0.05 indicates that Social Support has a significant effect on Career Adaptability, while the results of self-efficacy data processing in job search have a beta value of 0.310 with a sig value of 0.000, a sig value. 0.000 <0.05 indicates that self-efficacy in job search on career adaptability has a significant effect.